Prediction of Major Adverse Cardiovascular Events in Patients with Peripheral Artery Disease Using Circulating Immunomodulatory Proteins - Ben Li; Farah Shaikh; Houssam Younes; Batool Abuhalimeh; Jason Chin; Khurram Rasheed; Abdelrahman Zamzam; Rawand Abdin; Mohammad Qadura (Biomedicines)
Background/Objectives: The leading cause of death for people with peripheral artery disease (PAD) is major adverse cardiovascular events (MACE), including heart attacks and strokes. However, research into biomarkers that could help predict MACE in patients with PAD has been limited. Immunomodulatory proteins are known to significantly influence systemic atherosclerosis, suggesting they could be useful prognostic indicators for MACE in patients with PAD. In this study, we evaluated a broad panel of immunomodulatory proteins to identify those linked to MACE in individuals with PAD. Methods: We conducted a prognostic study involving a prospectively recruited cohort of 406 patients consisting of 254 with PAD and 152 without PAD. At the baseline, we measured the plasma concentrations of 17 circulating immunomodulatory proteins and followed the cohort for two years. The primary outcome was 2-year MACE, a composite of myocardial infarction, stroke, or death. Plasma protein concentrations were compared between patients with PAD with and without 2-year MACE using Mann–Whitney U tests. We further examined the prognostic potential of differentially expressed proteins through a Cox proportional hazards analysis, determining their independent associations with 2-year MACE while controlling for all the baseline demographic and clinical characteristics, including the existing coronary artery and cerebrovascular diseases. Additionally, A Kaplan–Meier analysis was performed to evaluate the 2-year freedom from MACE in patients with low versus high levels of the differentially expressed proteins based on the median plasma concentrations. Results: The mean age of the cohort was 68.8 years (SD 11.1), with 134 patients (33%) being female. During the two-year follow-up, 63 individuals (16%) developed MACE. The following proteins were significantly elevated in patients with PAD who experienced 2-year MACE compared to those who did not: galectin-1 (0.17 [SD 0.06] vs. 0.10 [SD 0.07] pg/mL, p = 0.012), alpha-1-microglobulin (16.68 [SD 7.48] vs. 14.74 [SD 6.71] pg/mL, p = 0.019), and galectin-9 (0.14 [SD 0.09] vs. 0.09 [SD 0.05] pg/mL, p = 0.033). The Cox proportional hazards analysis indicated that these three proteins were independently associated with 2-year MACE after adjusting for all the baseline demographic and clinical factors: galectin-1 (HR 1.45 [95% CI 1.09–1.92], p = 0.019), alpha-1-microglobulin (HR 1.31 [95% CI 1.06–1.63], p = 0.013), and galectin-9 (HR 1.35 [95% CI 1.02–1.78], p = 0.028). Over the two-year follow-up, patients with higher levels of galectin-1, galectin-9, and alpha-1-microglobulin had a lower freedom from MACE. Additional analysis showed that these three proteins were not significantly associated with 2-year MACE in patients without PAD. Conclusions: Among the 17 immunomodulatory proteins evaluated, galectin-1, galectin-9, and alpha-1-microglobulin were found to be independently and specifically associated with 2-year MACE in patients with PAD. Assessing the plasma concentrations of these proteins can aid in risk stratification for MACE in patients with PAD, helping to inform clinical decisions regarding multidisciplinary referrals to cardiologists, neurologists, and vascular medicine specialists. This information can also guide the aggressiveness of medical management, ultimately improving cardiovascular outcomes for patients with PAD.